Detection of Salmonella spp., Candida albicans, Aspergillus spp., and Antimicrobial Residues in Raw and Processed Cow Milk from Selected Smallholder Farms of Zimbabwe. (29th August 2012) - Mhone, Tryness Anastazia; Matope, Gift; Saidi, Petronella Tapiwa
Abstract : A cross-sectional study was conducted to detect the presence of Salmonella spp., Candida albicans, Aspergillus spp., and antimicrobial residues in raw milk (n = 120 ) and processed cow milk (n = 20 ) from smallholder dairy farms from three sites in Zimbabwe. Culture and isolation of Salmonella spp., C. albicans, and Aspergillus spp. were performed using selective media, while antimicrobial residues were detected by a dye reduction test. No Salmonella, but C. albicans (17.5%; 21/120), Aspergillus spp. (0.8%; 1/120), and antimicrobial residues (2.5%; 3/120) were detected from raw milk. C. albicans was isolated from all three sites, while Aspergillus spp. and antimicrobial residues were detected from sites 1 and 3, respectively. From processed milk, only C. albicans (5%) was isolated while Aspergillus spp. and antimicrobial residues were not detected. These results suggested low prevalence of Salmonella spp. and Aspergillus spp. and a relatively high prevalence of C. albicans in raw milk from the smallholder farms. The potential public health risks of C. albicans and the detected antimicrobial residues need to be considered. Thus, educating farmers on improving milking hygiene and storage of milk and establishing programmes for monitoring antimicrobial residues may help to improve the safety of milk from smallholder farms.